Income and asthma-related outcomes in children: a longitudinal study in the United Kingdom - Diarra, SS (2021)
There is evidence that children from socially disadvantaged families tend to have poorer health outcomes than their richer counterparts. However, evidence on the association between family income and specific outcomes, such as asthma and wheezing, is limited. This thesis therefore applies different methodological approaches to investigate the relationship between family income and asthma-related outcomes in children, in the United Kingdom.